The Attitude of Business Students toward the Ethics of Tax Evasion - Hauptman , Lidija (Naše gospodarstvo/Our economy, 2014)
The paper examines the ethics of tax evasion, which the literature explains using three views by Crowe. It presents the results of a survey conducted among business students in Slovenia. The study investigates the business students’ view of the ethics of tax evasion and whether the attitude toward these ethics varies according to gen- der. The study reveals that business students in Slovenia represent the view that tax evasion is ethical under certain conditions and in certain circumstances; differences in gender related to the ethics of tax evasion were identified as well.